DESIGN OF A TEACHER LEADERSHIP INSTRUMENT: A NEED ANALYSIS STUDY BASED ON MALAYSIAN CONTEXT - Rahim, Saiful Adli Ab (EARR (Educational Administration Research and Review), 2023)
Today’s education challenges require teachers to be leaders. However, some teachers are still unaware of their leadership qualities and practices, much less the feasibility of polishing said leadership. A guideline should be developed to enlighten teachers not only on the concept of teacher leadership but also on how to build teacher leadership qualities realistically. This study was conducted using the qualitative method involving an interview with eight (8) school leaders and teacher leaders for their perspectives on the need for designing a teacher leadership instrument. Five themes were identified in consequence; (i) improving current instruments, (ii) benchmarking effective teacher leadership practices, (iii) increasing awareness of teacher leadership, (iv) developing guidelines to improve teacher leadership competency, and, (v) building self-leadership as teacher leaders in the local context. Designing a teacher leadership instrument would be more cost-effective and save time compared to developing a prototype product. Future studies should focus on developing a teacher leadership instrument suited for 21st century learning needs, while considering different leadership categories including distributed leadership, instructional leadership, and learning-centred leadership. The instrument should be developed according to correct procedures with content and statistical assessment so that it can be widely used.